Childhood Disadvantage and Health Problems in Middle and Later Life: Early Imprints on Physical Health? - Ferraro, Kenneth F. (Am Sociol Rev, 2015)
Drawing from cumulative inequality theory, we examine the relationship between childhood disadvantage and health problems in adulthood. Using two waves of data from Midlife Development in the United States, we investigate whether childhood disadvantage is associated with adult disadvantage, including fewer social resources, and the effect of lifelong disadvantage on health problems measured at the baseline survey and a 10-year follow-up. Findings reveal that childhood socioeconomic disadvantage and frequent abuse by parents are generally associated with fewer adult social resources and more lifestyle risks. Health problems, in turn, are affected by childhood disadvantage and by lifestyle risks, especially smoking and obesity. Not only was early disadvantage related to health problems at the baseline survey, but childhood socioeconomic disadvantage and frequent abuse also were related to the development of new health problems at the follow-up survey. These findings reveal the imprint of early disadvantage on health decades later and suggest greater attention to resources, even during midlife, can interrupt the chain of risks.